Linkage among melanin biosynthetic mutations in Cochliobolus heterostrophus - A Guillen; B G Turgeon; P. R. Thorson; C. R. Bronson; O. C. Yoder (Fungal Genetics Reports, 1994)
Melanin is synthesized by C. heterostrophus from acetate via pentaketide and several dihydroxynaphthalene intermediates (Tanaka et al. 1991 Mycol. Res. 95:49-56), as it is for certain other fungi (Bell and Wheeler 1986 Ann. Rev. Phytopathol. 24:411-451; Kubo et al. 1989 Exp. Mycol 13:77-84; Chumley and Valent 1990 Mol. Plant-Microbe Int. 3:135-143). Previously, five melanin deficient mutants of C. heterostrophus were analyzed by Tanaka et al. (Mycol. Res. 95:49-56), who were unable to establish complete linkage relationships because three of the mutations (alb1, alb3, and brn1) showed no recombination when crossed to each other, and were unlinked to the other two (sal1 and pgr1), which mapped about 12 cM apart. A sixth color mutation, scr1, represented a third linkage group, but there was no evidence of its involvement in melanin biosynthesis. Independently, we have recovered six melanin-deficient mutants, one of which (alb1, Leach et al. 1982 J. Gen. Microbiol. 128:1719-1729) was included in the study of Tanaka et al. and maps to chromosome 1 on the C. heterostrophus RFLP map (Tzeng et al. 1992 Genetics 130:81-96). We report here that our remaining five melanin-deficient mutants [crm1 (light cream), crm2 (dark cream), brn1 (brown), rsy1 (rose), and probably gra3 (gray)] are linked to, but are not allelic with, alb1 (white) and constitute a gene cluster on chromosome 1